Considerations about Teacher Education from Teacher Narratives: Teaching Knowledge in Motion (Global Journal of Human-Social Science, 2022)
We present the results of a study to contribute to the reflections and discussions about the formative processes for teaching in the post-pandemic context To this end we conducted a piece of research constituted by a corpus formed out of 13 pedagogical letters sent to an event that took place in June 2022 by teachers who work in schools and carry out strict sensu postgraduate studies
Keywords: teacher training; teacher knowledge; evolution of the pandemic context